TEACHING L2 VOCABULARY THROUGH SMS LANGUAGE: SOME DIDACTIC GUIDELINES - López Rúa, Paula (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This article focuses on texting or SMS language, which is nowadays the most popular means of communication for a whole generation of mobile phone users. The introductory section comprises a parameter-based description of texting and a brief explanation of the features shared with other modalities of text-based electronic communication, after which the article provides an overview of the linguistic peculiarities of the system, i.e. its shortening mechanisms. It is suggested that an incursion into a subcode with which youngsters feel so identified could be beneficial for both L2 and L1 learning. This suggestion is illustrated by a series of exercises of different formats intended to practise the codification and interpretation of English texting. The conclusion drawn is that the exploitation of texting in the L2 classroom may be extremely interesting for several reasons: first, it may contribute to improving the students’ spelling and pronunciation skills in both the L1 and the L2, and it may also contribute to increasing their lexicon in the L2; second, students may acquire a better understanding of the notion of linguistic appropriateness and at the same time gain an insight into the functioning of languages and their flexibility to adapt themselves to different communicative situations. Resumen El presente artículo trata sobre el lenguaje SMS, actualmente el medio de comunicación más popular para toda una generación de jóvenes usuarios de teléfonos móviles. La introducción comprende una descripción del subcódigo y una breve explicación de los rasgos compartidos con otras modalidades de comunicación electrónica escrita, tras lo cual se proporciona una visión general de los mecanismos de abreviación empleados en este sistema. La principal idea defendida en este artículo es que la explotación pedagógica de un subcódigo con el que los jóvenes se sienten identificados puede ser beneficiosa para el aprendizaje de la L1 y la L2. Esta sugerencia se acompaña de ejercicios de diferentes formatos destinados a la práctica de la codificación e interpretación del lenguaje SMS en inglés. Se concluye que las ventajas de esta actividad son múltiples: por una parte, se puede contribuir a mejorar los conocimientos de ortografía y pronunciación de los alumnos en la L1 y la L2; por otro lado, los alumnos pueden aumentar su vocabulario en la L2, comprender cómo las lenguas son instrumentos flexibles que se adaptan a distintas situaciones comunicativas y entender lo que implica la utilización apropiada de un código lingüístico.